Identification and validation of a dysregulated TME-related gene signature for predicting prognosis, and immunological properties in bladder cancer - Shen, Chong; Chai, Wang; Han, Jingwen; Zhang, Zhe; Liu, Xuejing; Yang, Shaobo; Wang, Yinlei; Wang, Donghuai; Wan, Fangxin; Fan, Zhenqian; Hu, Hailong (Frontiers in Immunology, 2023)
The interactions between tumor cells and their tumor microenvironment (TME) lead to the tumor heterogeneity, which promotes tumor occurrence and progression. Recently, TME has gained extensive attention as a possible therapeutic target for cancers. However, a valid TME-related prediction model is urgently needed for accurate assessment of patients' prognoses and therapeutic value to assist clinical decision-making. The transcriptome data and corresponding clinical data of BC patients were downloaded from the public databases. TME-related genes (TMRGs) were obtained from MSigDB database. There was a total of 133 TME-related prognostic differentially expressed genes in BC. Then, consensus clustering analysis was performed to identify TME-related three molecular clusters, which have remarkedly different clinicopathological characteristics and survival prognosis. Also, we established a prognostic nine TMRGs-related signature (including C3orf62, DPYSL2, GZMA, SERPINB3, etc.) through LASSO Cox regression analysis. And, its reliable predictive performance in other several BC cohorts was validated. Potential response of ICB therapy was estimated with Tumor Immune Dysfunction and Exclusion (TIDE) algorithm and Immunophenoscore (IPS). Additionally, we also found that the expression level of partial genes in the model was significantly correlated with objective responses to anti-PD-1 or anti-PD-L1 treatment in the IMvigor210, GSE111636, GSE176307, or our Truce01 (registration number, NCT04730219) cohorts. GO and KEGG enrichment analysis indicated that ECM and collagen binding-related biological processes and pathways were significantly enriched in the high-risk group. Finally, we noticed that the TMEscore was significantly assotiated with the drug susceptibility, immune cell infiltration, and efficacy prediction of immunotherapy. Notably, differential expression validation by real-time PCR within 10 paired BC tissues and in vitro phenotypic experiments identified that SERPINB3 significantly promoted BC cells migration, and invasion. Overall, we identified a novel prognositic model based on the nine-TMRGs that could accurately and stably predict survival and guide individual treatment with BC patients. Our study may contribute to provide new therapeutic strategies for BC.